Evaluación de los ciclos de refrigeración convencionales con sustancias refrigerantes naturales, utilizando la simulación computacional (2019)
The present work presents the evaluation of conventional refrigeration cycles (mechanical vapor compression) for the operation of three refrigerants natural products used for freezing food. For this purpose, initially a pre-selection of the most common natural refrigerants where take into account the environmental, physicochemical and safety aspects of Natural refrigerant substances analyzed. Then, for the final selection of the Initially preselected refrigerants, an analysis of the loads was carried out thermal sensors to define which ones work more efficiently in a cycle of vapor compression refrigeration, applied to the freezing industry of foods.